PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDIT JAMI’ATUL MUSLIMIN DUMAI - Mulyani '; Hendri Marhadi Hendri Marhadi; Gustimal witri Gustimal witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. This research is founded or the low of the social study of the student, by average class 60,10 but the mark of the succes minimum (KKM) social is seventy. Between the student amount 30 person only 11 students who get the target (KKM) by the target classical 36,6%.  This research is the research of the student action (PTK) who did the purpose to increase the result of social the class four SDIT Jami’atul Muslimin by cooperative model The tipe Think Pair Share. The result of the social of grade four SDIT Jami’atul Muslimin Dumai. This research att ended at 8 th  of April 2013 until 2 nd of Mai 2014 by two siclus. The subject of this research is the student  grade four  SDIT Jami’atul  Muslimin Dumai which amount thirty person. The instrument of to collect the data at this scription is the sheet of the teacher activity and the student and so the student result. This scription to serve the student research which get from the daily make before action by average 60,10 to increase at the first siclus by average 70,33 at the second ciclus increase  by average 84,17. The teacher activity in the studying  process at the first ciclus at the first meeting 62,5% and the second meeting increase become 70,8%. The second ciclus the first meeting 79,2% and the second meeting increase become 87,5%. The result of analysis data of the student at the first ciclus at the first  meeting 58,3% and the second  meeting 66,7% at the  second ciclus at the  first meeting  75% and the second meeting  increase become 83,3% . The result of research at the class four of SDIT Jami’atul  Muslimin improve that the attend  of the cooperative studying model the tipe of think pair share can increase the result of social of the grade  four SDIT Jami’atul Muslimin Dumai. Key words : The studying cooperative model the tipe Think Pair Share (TPS)